1986
DOI: 10.1159/000183855
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Commercial Peritoneal Dialysis Solutions towards Peritoneal Cells of Chronically Uremic Mice

Abstract: A gradual loss of cell viability was observed during in vitro incubation of peritoneal cells from chronically uremic mice in commercial peritoneal dialysis solutions. The magnitude of this cytotoxicity toward peritoneal cells harvested from uremic mice and controls was comparable. Resident peritoneal cells were always found to be more susceptible than thioglycolate-elicited peritoneal populations of either macrophages or polymorphonuclear cells. In order to elucidate the factors contributing to this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…Indeed, several in vitro experiments have demonstra ted that fresh peritoneal dialysate reduces the viability of lymphocytes [3], polymorphonuclear leukocytes (PMNL) [4] and peritoneal macrophages [5], inhibits the phagocytosis and bacterial killing of PMNL [6] and peri toneal macrophages [4] and impairs their respiratory and oxidative metabolism [7,8], In contrast, little is known about the effects of dialysates on the ability of leukocytes to generate inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several in vitro experiments have demonstra ted that fresh peritoneal dialysate reduces the viability of lymphocytes [3], polymorphonuclear leukocytes (PMNL) [4] and peritoneal macrophages [5], inhibits the phagocytosis and bacterial killing of PMNL [6] and peri toneal macrophages [4] and impairs their respiratory and oxidative metabolism [7,8], In contrast, little is known about the effects of dialysates on the ability of leukocytes to generate inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…This surgical approach results in a prompt and sustained state of renal failure of a magnitude essentially depending on the extent of the initial electrocoagulation. This is a promising animal model for the study of various aspects of chronic uremia, and it has proved useful to us in the last few years for the investigation of immune responses [7][8][9][11][12][13][14][15] and accelerated atherosclerosis [23] in chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has often been shown that some degree of residual cellular dysfunction still persists even though the acidic pH has been corrected to physiologic or close-to-physiologic pH levels. A case in point is the persistence of residual cytotoxic effects on mouse peritoneal cells and human mesothelial cells in vitro in spite of the neutralization of the acidic pH (14,35). Such lingering detrimental effects may be related to the toxic properties of autoclaving-generated breakdown products of glucose or to the toxic influences of other constituent(s) (other than the combination of hydrogen and lactate) of conventional PDS.…”
Section: Cellular Dysfunctions Due To the Formation Of Toxic Glucose mentioning
confidence: 99%
“…1). This prompt and severe intracellular acidosis is probably responsible for the impairment of various functions of leukocytes, macrophages and peritoneal cells (such as the functions of cell viability (14), bacterial killing (15,16), chemiluminescence (15)(16)(17), release of interleukin-6, leukotriene and tumor necrosis factor (18,19), oxygen consumption (16,17,20), phagocytosis (15,16,21) and superoxide generation (22)(23)(24)(25) when these cells are exposed to conventional PDS.…”
mentioning
confidence: 99%